Preparation method of dielectric material with functional filler orientation assisted by ionic liquid

By introducing ionic liquids and functional fillers into dielectric materials and coordinating orientation under electric fields, the problem of insufficient energy density of existing dielectric materials is solved, and the comprehensive performance improvement of high dielectric constant, low dielectric loss and good thermal stability is achieved, and its application in a variety of electronic devices has been expanded.

CN119859294APending Publication Date: 2025-04-22QINGDAO UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510021944.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing dielectric materials have limitations in improving energy density, and traditional methods are difficult to meet the needs of high energy storage characteristics, especially when fillers and substrates are insufficiently interacted.

Method used

By introducing ionic liquids, providing polarization forces and functional fillers to be orientated under electric fields, polymer-based composite dielectric materials with high dielectric constant, low dielectric loss, insulation properties and good thermal stability are prepared.

Benefits of technology

It has achieved improvements in dielectric performance and thermal conductivity, significantly improved dielectric constant, reduced dielectric loss, provided dielectric materials with excellent comprehensive performance, and expanded its applications in pulse power devices, portable electronic devices and electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859294A_ABST
    Figure CN119859294A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional polymers, and particularly relates to a preparation method of a dielectric material with functional filler orientation assisted by ionic liquid, when a composite dielectric material is prepared by orienting the functional filler with an external electric field, the ionic liquid is added to provide large polarization force and cooperate with the functional filler for orientation, so that the composite dielectric material is prepared. A more perfect orientation structure is formed, the dielectric property and the heat-conducting property of the material are improved, and the dielectric loss is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional polymer materials, and in particular to a method for preparing an ionic liquid-assisted functional filler-oriented dielectric material. Background Art

[0002] Dielectric capacitors are widely used in pulse power devices, portable electronic devices, electric vehicles and other fields due to their ultra-high power density, fast charge and discharge rate, high operating voltage and excellent cycle stability. However, the problem of low energy density limits its wider application. The key to improving the energy density of dielectric capacitors is to develop dielectric materials with excellent comprehensive properties. Traditional inorganic ceramic or polymer dielectric materials are difficult to meet the requirements, so the development of new composite dielectric materials has become a research hotspot.

[0003] Chinese patent CN114536912B provides a method for synergistically improving the breakdown strength and dielectric constant of polymer dielectrics, sputtering nano-gold particles on the surface of the polymer material, and preparing metal / polymer dielectric composite materials by casting and hot pressing. The dielectric constant is improved by the micro-capacitance formed between the nano-gold particles and the polymer, and the Coulomb blockade effect caused by the nano-gold particles is used to enhance the breakdown strength, thereby achieving a synergistic improvement in the dielectric constant and breakdown strength. Chinese patent CN117079912A uses soft segments with UV curing activity and hard segments to copolymerize and cross-link, and coats and in-situ photocures to form a polyacrylate dielectric film. The resulting film has higher dielectric stability, breakdown strength and energy density, and lower conduction loss at high temperatures.

[0004] In summary, the preparation of dielectric materials is currently limited to relying mainly on direct physical mixing of polymer matrix and filler. However, due to the poor interaction between filler and matrix, the performance of composite materials prepared by this method is difficult to meet the needs of practical applications; binary polymer-based dielectric materials have low breakdown strength or rely on a large number of ceramic particles to fill, which seriously affects flexibility and processing performance. Therefore, in-depth and detailed exploration is still needed to achieve large-scale preparation and wide application of polymer composite dielectrics with high energy storage characteristics. Summary of the invention

[0005] The present invention provides a method for preparing a polymer-based composite dielectric material with high dielectric constant, low dielectric loss, high insulation performance and good thermal stability. By introducing ionic liquids to provide a large polarization force, and coordinating with functional fillers to orient under an electric field, a polymer-based composite dielectric material with excellent comprehensive performance is successfully prepared. Among them, the functional fillers can construct an effective orientation structure in the thickness direction of the composite film, thereby improving the dielectric performance and thermal conductivity.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing an ionic liquid-assisted functional filler-oriented dielectric material comprises the following steps:

[0008] 1) adding ionic liquid, dielectric filler and curing agent into a polymer matrix and mixing them uniformly to obtain a suspension;

[0009] 2) Casting the suspension on the ITO conductive glass, and then attaching another piece of ITO conductive glass to form a mold;

[0010] 3) Connecting the mold to an external electric field device and placing it on a magnetic heating stirrer, applying a sinusoidal AC electric field, heating and curing, cooling and peeling, and obtaining a composite film with an oriented structure.

[0011] Furthermore, the ionic liquid is 1-propyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide salt, and its mass accounts for 5%-10% of the mass of the suspension.

[0012] Furthermore, the dielectric filler is AlN and / or BaTiO3, and its mass accounts for 5%-50% of the mass of the suspension, and most preferably 20%.

[0013] Furthermore, the polymer matrix is ​​PDMS.

[0014] Furthermore, the polymer matrix and curing agent are selected from the PDMS matrix and curing agent in Dow Corning SYLGARD 184 rubber, with a mass ratio of 10:1.

[0015] Furthermore, the mixing method in step 1) is: using a non-invasive homogenizer to rotate the above mixture at a certain speed for a certain time in a non-vacuum mode, and then adjusting to a vacuum mode to increase the speed and continue to rotate to remove bubbles, preferably: rotating at a speed of 500 rpm / min for 2 minutes, and then adjusting to a vacuum mode and rotating at a speed of 1500 rpm / min for 2 minutes to remove bubbles.

[0016] Furthermore, in step 2), the upper and lower ITO conductive glass sheets are placed with the conductive surfaces facing the suspension, and the two ITO conductive glass sheets are separated by insulating glass.

[0017] Furthermore, the external electric field equipment in step 3) is composed of an arbitrary waveform generator, a high voltage amplifier and an oscilloscope.

[0018] Furthermore, in step 3), the frequency of the sinusoidal alternating electric field is 10 Hz and the voltage is 3000 Vp-p / mm.

[0019] Furthermore, the temperature of heating and curing in step 3) is 100°C.

[0020] The dielectric material obtained by the method of the present invention can be used in the fields of pulse power devices, portable electronic devices, electric vehicles, etc.

[0021] Compared with the prior art, this application has the following advantages and beneficial effects:

[0022] 1. Significantly improve the dielectric constant, reduce dielectric loss, and provide dielectric materials with excellent comprehensive performance.

[0023] 2. Optimize the structure and performance of composite materials, realize multifunctional synergy, and expand application areas.

[0024] 3. The process is simple, the cost is low, and it is easy to mass produce and promote application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 These are cross-sectional SEM images of the 15wt% IL / BaTiO3 / PDMS three-phase composite membrane at different magnifications in Example 1, where (ad) is a non-oriented composite membrane; and (eh) is an oriented composite membrane.

[0026] Figure 2 The curves of the dielectric constant of (a) oriented composite film and (b) unoriented composite film with different filler contents in Example 1 as a function of frequency. The curves of the dielectric loss of (c) oriented composite film and (d) unoriented composite film with different filler contents as a function of frequency.

[0027] Figure 3 When the IL content is 10 wt % in Example 2, the dielectric constant of (a) the unoriented composite film and (b) the oriented composite film varies with frequency at different AlN filling amounts.

[0028] Figure 4 (a) is a curve showing the relationship between the out-of-plane thermal conductivity of different samples and the AlN content in Example 2; (b) is a schematic diagram showing the comparison of the out-of-plane thermal conductivity of different samples when the AlN content is 50 wt%.

[0029] Figure 5 The curves showing the change of dielectric constant with frequency for (a) unoriented composite film and (b) oriented composite film at different barium titanate contents in Comparative Example 1.

[0030] Figure 6 2 is a curve showing the change of dielectric constant with frequency for (a) unoriented composite film and (b) oriented composite film at different IL contents in Comparative Example 2.

[0031] Figure 7 The curves of the dielectric constant of (a) oriented composite film and (b) unoriented composite film as a function of frequency at different filler contents in Comparative Example 3; and the curves of the AC conductivity of (c) oriented composite film and (d) unoriented composite film as a function of frequency. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below through specific embodiments.

[0033] The Dow Corning SYLGARD 184 rubber used in the following examples is a two-component kit product consisting of liquid components, including a basic component (PDMS matrix) and a curing agent, and the weight ratio of the basic component (PDMS) to the curing agent is 10:1.

[0034] Dielectric constant test: Dielectric impedance spectrometer is used to test the dielectric constant. Before the test, the sample is cut into discs with a circular cutter with an inner diameter of 25 mm, and a circular copper sheet with a diameter of 30 mm is used as an electrode to measure the dielectric constant (ε) of the composite film under study.

[0035] Example 1: Preparation of IL / BaTiO3 / PDMS three-phase composite membrane:

[0036] (1) First, take the PDMS matrix in Dow Corning SYLGARD 184 rubber, add a certain amount of ionic liquid 1-propyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide salt, barium titanate and curing agent in Dow Corning SYLGARD 184 rubber, the sum of ionic liquid and barium titanate accounts for 15% of the PDMS mass, and each accounts for 7.5%. In order to make the above mixture uniformly mixed, use a non-invasive homogenizer to rotate the above mixture at a speed of 500 rpm / min for 2 minutes in a non-vacuum mode, and then adjust it to a vacuum mode and rotate it at a speed of 1500 rpm / min for 2 minutes to remove bubbles. The mixed suspension is cast on a clean ITO conductive glass (conductive surface placed upward), and then another piece of ITO conductive glass (conductive surface placed downward) is slowly attached thereto to obtain a mold containing the suspension, wherein the upper and lower ITO glass sheets are separated by an insulating glass with a thickness of 1 mm.

[0037] (2) In order to prepare a sample with an oriented structure, the ITO conductive glass is first connected to an external electric field device (composed of an arbitrary waveform generator, a high-voltage amplifier and an oscilloscope), and then placed horizontally on a digital display magnetic heating stirrer, and then a sinusoidal AC electric field with a frequency of 10 Hz and a voltage of 3000 Vp-p / mm is applied. After applying the electric field for 20 minutes, the digital display magnetic heating stirrer is heated to 100°C, and heating is stopped until the sample is completely solidified, and the electric field device is turned off. Finally, after it cools to room temperature (the room temperature in the present invention is 25°C), the composite film is peeled off from the ITO glass to obtain an IL / BT / PDMS three-phase composite film with an oriented structure.

[0038] Preparation of unoriented composite film: Based on the above operation, step (2) was replaced by: directly heating and curing at 100°C for 50 min, and finally cooling and peeling to obtain an unoriented IL / BT / PDMS three-phase composite film.

[0039] The microstructures of the unoriented and oriented composite films were characterized by scanning electron microscopy. Figure 1 The cross-sectional SEM images of 15wt% IL / BaTiO3 / PDMS three-phase composite membrane at different magnifications, where (ad) is an unoriented composite membrane; (eh) is an oriented composite membrane. The existence of an oriented structure in the oriented IL / BaTiO3 / PDMS three-phase composite membrane is confirmed, in which IL microspheres and BaTiO3 are interspersed with each other and arranged into a long chain-like oriented structure along the thickness direction.

[0040] According to the above operation, the masses of IL and barium titanate were kept the same, and the sum of their addition amounts was changed to 10%, 15%, and 20% of the matrix mass respectively, while other conditions remained unchanged, to prepare oriented composite films and unoriented composite films with different filler contents.

[0041] The dielectric properties of the unoriented and oriented composite films prepared at different filler contents were characterized ( Figure 2 ), the results show that the distribution of fillers in the polymer matrix can significantly improve the dielectric constant of the composite film.

[0042] Example 2: Preparation of AlN / IL / PDMS ternary composite film:

[0043] (1) First, ionic liquid 1-propyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide salt, aluminum nitride and curing agent were added to the PDMS matrix in Dow Corning SYLGARD 184 rubber according to the designed mass percentage. The mass of IL and aluminum nitride was kept the same, and the sum of the addition amount of the two was changed to 10%, 20%, 30%, 40% and 50% of the mass of the matrix, respectively. In order to mix the above mixture evenly, a non-intrusive homogenizer was used to rotate it at a speed of 500 rpm / min for 2 minutes in a non-vacuum mode, and then adjusted to a vacuum mode and rotated at a speed of 1500 rpm / min for 2 minutes to remove bubbles.

[0044] (2) Then cast the mixed suspension onto a clean ITO conductive glass (with the conductive surface facing up), and then slowly attach another piece of ITO conductive glass (with the conductive surface facing down) onto it to obtain a mold containing the suspension, wherein the upper and lower ITO glass sheets are separated by an insulating glass with a thickness of 1 mm. Place the mold horizontally on a digital magnetic heating stirrer, connect the ITO conductive glass to the power cord of the external electric field device, and then apply a sinusoidal AC electric field with a frequency of 1 kHz and a voltage of 3000 Vp-p / mm. After applying the electric field for 20 minutes, heat the digital magnetic heating stirrer to 100°C and stop heating until the sample is completely solidified. Finally, wait for it to cool to room temperature and peel off the composite film from the ITO glass to obtain a ternary AlN / IL / PDMS composite film with an oriented structure.

[0045] Preparation of unoriented composite film: Based on the above operation, step (2) was replaced by: directly heating and curing at 100°C for 50 min, and finally cooling and peeling to obtain an unoriented AlN / IL / PDMS three-phase composite film.

[0046] The dielectric properties of the prepared AlN / IL / PDMS composite membrane were tested ( Figure 3 ), the results show that with the increase of AlN content, the micro-capacitor structure between ILs in the oriented structure and the ion polarization effect significantly enhance the dielectric constant of the composite film, while the interpenetration of highly insulating AlN and IL suppresses the ion polarization of IL to a certain extent, maintaining low dielectric loss and good insulation performance.

[0047] According to the above method, the mass of the ionic liquid was fixed at 10% of the mass of the PDMS substrate, and the addition amount of aluminum nitride was changed to 0%, 10%, 20%, 30%, 40%, and 50% of the mass of the substrate, respectively, to prepare oriented and unoriented ternary AlN / IL / PDMS composite films; the mass of the ionic liquid was fixed at 0, and the addition amount of aluminum nitride was changed to 0%, 10%, 20%, 30%, 40%, and 50% of the mass of the substrate, respectively, to prepare oriented and unoriented binary AlN / PDMS composite films, and the out-of-plane thermal conductivity ( Figure 4 ), the results show that the long chain structure formed along the thickness direction under the action of the external electric field acts as an effective heat conduction path in the polymer matrix, significantly improving the thermal conductivity of the polymer-based composite dielectric.

[0048] Comparative Example 1 Preparation of BaTiO3 / PDMS two-phase composite membrane

[0049] On the basis of Example 1, the ionic liquid was removed to prepare oriented and non-oriented BaTiO3 / PDMS two-phase composite membranes with different BaTiO3 contents.

[0050] Then the dielectric properties were characterized and the results are shown in Figure 5 The dielectric constant of the oriented composite film is improved compared with that of the unoriented composite film, which is due to the vertical chain structure formed after the electric field orientation. For example, at 100Hz, the dielectric constant of the pure PDMS film is about 2.92, the dielectric constant of the unoriented composite film filled with 20wt% BaTiO3 is only about 4.025, and the dielectric constant of the oriented composite film is 4.71 ( Figure 5 ab).

[0051] In addition, the dielectric loss of the BaTiO3 / PDMS two-phase composite film is slightly higher than that of the unoriented sample, but it is still at an extremely low level (<0.01). This is because barium titanate, as a high dielectric ceramic material, has a very low dielectric loss. Even after being oriented into a chain structure by electric field, the dielectric loss of the composite material is maintained at a low level due to its own high insulation properties.

[0052] Comparative Example 2 Preparation of IL / PDMS two-phase composite membrane

[0053] On the basis of Example 1, BaTiO3 was removed to prepare oriented and unoriented IL / PDMS two-phase composite membranes with different ionic liquid contents. Then the dielectric properties were characterized. Figure 6 The relationship between the dielectric constant of IL / PDMS two-phase composite films with different structures and the frequency is shown. It can be seen that the dielectric properties of the unoriented and oriented composite films are significantly different.

[0054] For the unoriented composite film, its dielectric constant does not change significantly within the tested frequency range, indicating that the IL randomly dispersed in PDMS exhibits a low frequency dependence; while for the oriented composite film, its dielectric constant decreases significantly with increasing frequency, and this trend becomes more obvious with increasing IL content. At the same IL filling amount, compared with the unoriented composite film, the dielectric constant of the oriented composite film shows an explosive growth, which is particularly significant at low frequencies. For example, Figure 6 As shown in Figure 2, at 100 Hz, the dielectric constant of the 20 wt% IL / PDMS unoriented composite film is only 4.32, while the dielectric constant of the corresponding oriented composite film is as high as 12000. This amazing improvement can be attributed to the surge in the number of micro-capacitor structures in the chain structure formed after IL orientation and the more significant ion polarization effect.

[0055] In addition, the dielectric loss of the unoriented composite film increases slightly with the increase of IL content, but still maintains an ultra-low level (<0.002); while the dielectric loss of the oriented composite film increases significantly with the increase of IL content. For example, at 100Hz, the dielectric loss of the 20wt% IL / PDMS oriented composite film is as high as 4.81, while the corresponding dielectric loss of the unoriented composite film is only 0.00195. It is worth noting that with the increase of IL content, the dielectric loss of the oriented composite film gradually moves to the right in the frequency range of 102-104.

[0056] Comparative Example 3 Characterization of dielectric properties of IL / BaTiO3 / PDMS three-phase composite membrane

[0057] The IL / BaTiO3 / PDMS three-phase composite membrane was prepared by the method of Example 1, wherein the filling ratio of IL and BaTiO3 was 1:1. Figure 7 The relationship between the dielectric constant and dielectric loss of the unoriented (W) and oriented (Q) composite films and the frequency at different filler contents is shown in Figure 2. First, from Figure 7 It can be seen from (a)-(b) that the dielectric constant of the unoriented three-phase composite film does not change much with frequency, while the dielectric constant of the oriented three-phase composite film gradually decreases with the increase of frequency, showing a strong frequency dependence. This is because as the frequency increases, in the chain structure formed by the orientation, the ion transitions and dipole polarization between the ILs are unable to respond to the change of frequency in time, resulting in a decrease in the dielectric constant. In addition, from Figure 7 As can be seen in (a), with the increase of filler content, the dielectric constant of the unoriented IL / BaTiO3 / PDMS three-phase composite film gradually increases, and is higher than the corresponding two-phase composite film. Although the dielectric constant of the oriented three-phase composite film is also significantly improved, it is far lower than the corresponding two-phase composite film. For example, when the frequency is 100Hz, the dielectric constant of the 15wt% IL / BaTiO3 / PDMS unoriented three-phase composite film is only 4.87, and the dielectric constant of the oriented three-phase composite film is 124( Figure 7 b), although it is lower than the dielectric constant of the IL / PDMS two-phase composite film, the dielectric loss of the IL / PDMS two-phase composite film is very large. For example, at 100 Hz, the dielectric loss of the 20 wt% IL / PDMS oriented composite film is as high as 4.81, while the dielectric loss of the 15 wt% IL / BaTiO3 / PDMS oriented composite film is only 0.162.

[0058] It is worth noting that after testing the dielectric loss of the unoriented and oriented IL / BaTiO3 / PDMS three-phase composite films, it was found that the dielectric loss of the oriented three-phase composite film was improved compared with the unoriented composite film, but both were at a low level. For example, when the frequency was 100Hz, the dielectric loss of the 15wt% IL / BaTiO3 / PDMS unoriented three-phase composite film was 0.00272, and the dielectric loss of the corresponding oriented composite film was 0.162. This can be attributed to the chain structure of BaTiO3 randomly interspersed between ILs formed after orientation, which greatly suppressed the ionic polarization between ILs.

[0059] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited to the above embodiments. Any simple deformation, equivalent change or modification based on the present invention is still within the protection scope of the present invention.

Claims

1. A method for preparing an ionic liquid-assisted functional filler-oriented dielectric material, comprising the following steps: 1) adding ionic liquid, dielectric filler and curing agent into a polymer matrix and mixing them uniformly to obtain a suspension; 2) Casting the suspension on the ITO conductive glass, and then attaching another piece of ITO conductive glass to form a mold; 3) Connecting the mold to an external electric field device and placing it on a magnetic heating stirrer, applying a sinusoidal AC electric field, heating and curing, cooling and peeling, and obtaining a composite film with an oriented structure.

2. The preparation method according to claim 1, characterized in that: The ionic liquid is 1-propyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide salt, and its mass accounts for 5%-10% of the mass of the suspension.

3. The preparation method according to claim 1, characterized in that: The dielectric filler is AlN and / or BaTiO3, and its mass accounts for 5%-50% of the mass of the suspension.

4. The preparation method according to claim 1, characterized in that: The polymer matrix is ​​PDMS.

5. The preparation method according to claim 4, characterized in that: The polymer matrix and curing agent are selected from the PDMS matrix and curing agent in Dow Corning SYLGARD 184 rubber, with a mass ratio of 10:

1.

6. The preparation method according to claim 1, characterized in that: The mixing method in step 1) is: using a non-intrusive homogenizer to rotate the above mixture at a certain speed for a certain time in a non-vacuum mode, and then adjusting to a vacuum mode to increase the speed and continue to rotate to remove bubbles.

7. The preparation method according to claim 1, characterized in that: Step 2) Place the upper and lower ITO conductive glass sheets with their conductive surfaces facing the suspension, and separate the two ITO conductive glass sheets with insulating glass.

8. The preparation method according to claim 1, characterized in that: The external electric field equipment of step 3) is composed of an arbitrary waveform generator, a high voltage amplifier and an oscilloscope.

9. The preparation method according to claim 1, characterized in that: Step 3) The frequency of the sinusoidal AC electric field is 10 Hz and the voltage is 3000 Vp-p / mm.

10. The preparation method according to claim 1, characterized in that: Step 3) The temperature of heating and curing is 100°C.

Citation Information

Patent Citations

  • A method for synergistically improving the breakdown strength and dielectric constant of polymer dielectrics

    CN114536912B

  • Polymer-based dielectric and preparation method thereof

    CN117079912A